Sustained Gaze Is a Reliable In-home Test of Attention for Aging Pet Dogs - Hoel, Jane A.; Templeton, Ginger B.; Fefer, Gilad; Case, Beth C.; Shah, Anshu; Gruen, Margaret E.; Olby, Natasha J. (Frontiers in Veterinary Science, 2021)
Canine Cognitive Dysfunction Syndrome (CDS) is a syndrome of progressive cognitive decline comparable to Alzheimer’s Disease. The sustained gaze test captures attention loss associated with CDS in laboratory settings, and adapting the sustained gaze test for use by owners at home could greatly increase the data generated on CDS. We hypothesized that it would be feasible for owners to perform the sustained gaze test at home, and that results would be reliable over repeated trials. Training materials were developed and dog owners underwent training and performed the test in triplicate at weekly intervals for 3 weeks. Gaze videos and a CAnine DEmentia Scale (CADES) questionnaire were submitted each week. Videos were examined for inclusion and duration of gaze was recorded. One observer repeated video assessments twice, one week apart; 5 different observers assessed videos once. Outcome measures included the relationship between CADES and gaze duration, test-retest reliability of owner-performed sustained gaze testing, and intra- and inter-rater reliability. Twenty dogs aged 7 to 15.5 years completed testing. The majority of videos were acceptable (162/183). Within dog test-retest reliability was excellent (ICC = 0.96). Intra- and interobserver reliability for determining video validity for inclusion were substantial (k = 0.76 and 0.78 respectively); for duration of gaze these were excellent (ICC = 0.99 and 0.96 respectively). Gaze duration was significantly associated with CADES (p = 0.0026). We conclude that owners can perform the sustained gaze test at home and that data generated are reliable and correlate to CADES, a validated measure of dementia.